Financial instruments and institutions - Ryan, Stephen G (Wiley, 2007)
Includes bibliographical references and index; Financial instruments and institutions -- Nature and regulation of depository institutions -- Thrifts -- Interest rate risk and net interest earnings -- Credit risk and losses -- Fair value accounting for financial instruments -- Mortgage banks -- Securitizations -- Commercial banks -- Derivatives and hedging -- Market risk disclosures -- Lessors and lease accounting -- Insurers and insurance accounting -- Property-casualty insurers' loss reserve disclosures